The Relationship Between Maternal Nutritional Knowledge and Maternal Behavior on the Nutritional Status of Children Under Five at the Blangkejeren City Health Center - Ginting, Wira Maria; Br Hutabarat, Ferawati (JURNAL KESMAS DAN GIZI (JKG), 2025)
The problem of undernutrition and malnutrition among children under five remains a major public health challenge in Indonesia, including in the working area of the Blangkejeren City Health Center. This condition is influenced by inadequate dietary intake and the high prevalence of infectious diseases among toddlers. One of the key determinants in preventing nutritional problems is the role of mothers, particularly their level of knowledge and behavior in providing balanced and nutritious meals to their children. Limited maternal understanding of healthy eating patterns may reduce attention to the nutritional needs of toddlers, thereby leading to suboptimal feeding practices. This study aimed to examine the relationship between maternal nutritional knowledge and maternal behavior with the nutritional status of children under five at the Blangkejeren City Health Center. A quantitative research approach with a cross-sectional design was applied. The population consisted of all mothers who had children under five within the health center’s working area, with a total sample of 22 respondents. Data were analyzed to describe the distribution of knowledge, behavior, and nutritional status, as well as to test the relationships among variables. The findings revealed that the majority of mothers had good nutritional knowledge (77.3%), frequently practiced balanced feeding behavior (63.6%), and most children under five had normal nutritional status (72.7%). Statistical tests indicated significant associations between maternal nutritional knowledge and children’s nutritional status (p = 0.000), as well as between maternal behavior and children’s nutritional status (p = 0.000). These results suggest that the better the mothers’ knowledge and behavior regarding nutrition, the higher the likelihood that their children will achieve normal nutritional status.